Haunt you to the end ebook - Cady, Ryan (Haunt You to The End (2023), 2024)
Ghost Story for the End of the World! In a not-sofar future rife with climate disasters and worldwide instability, an eccentric billionaire and his crew—a disgraced journalist, a radical doctor, a TV demonologist, and a squad of hardbitten military contractors—set out to prove the existence of life after death. But even if their mission is a success, the truth behind the "most haunted place on earth" may not be the comforting revelation the world is hoping for. Collects HAUNT YOU TO THE END #1-5